Cervical lymphadenopathy in a patient receiving anti-TNF a treatment: glandular tuberculosis or oropharyngeal tularemia? - S. Alkan; İ. Şahinoğlu; M. Serhat Şahinoğlu (Infectious Diseases and Tropical Medicine, 2023)
BACKGROUND: Tularemia is a global anthroponotic disease that is endemic in some regions of Turkey, and it is carried by small rodents (hares) and arthropods (ticks, horseflies). Tularemia is caused by the Francisella tularensis bacteria, which is a facultatively intracellular Gram-negative bacillus.